Development of high performance lightweight nanocomposite sport shoe soles - Husniyah Aliyah Lutpi (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The selection of material for shoe soles is important as it determines the long-term performance of sports shoes, especially the performances of athletes' shoes with respect to comfort during walking, running, and jumping. An effective approach is developed to establish a strong high-density polyethylene (HDPE)/ethylene propylene rubber (EPR) matrix by introducing electron beam (EB) radiation to the nanocomposite as a crosslinking technique. This study focuses on the variation of carbon nanotubes (CNTs) in the HDPE/EPR polymer blend. The aim of this research is to find the optimum CNT content for the mechanical and thermal properties of EB-irradiated HDPE/EPR nanocomposite for shoe soles. The nanocomposites were melt blended before being compression moulded to form the specimens. The specimens were then irradiated under EBs at 100 kGy. The effect of CNT contents of 0.5, 1, 3, and 5 wt% on the mechanical properties of HDPE/EPR–CNT nanocomposites was investigated for application as the outer shoe sole. Meanwhile the content of organo montmorillonite (OMMT) filling the HDPE/EPR matrix was maintained at 4 wt% for insole shoe application. The combinations of nanofillers and polymer matrix enhance the performance of sports-shoes soles since they each exhibit superior properties. The irradiated and unirradiated nanocomposites were compared and analysed in terms of the mechanical and thermal properties. The irradiated nanocomposite with a CNT content of 3 wt% showed an improvement of the mechanical properties. The tensile strength and impact strength increased by nearly 50% compared to unirradiated and unreinforced CNTs. The thermal properties of the irradiated nanocomposite also showed an improvement in the glass transition temperature (Tg) of 9.6%, an increase in the melting temperature (Tm) from 133.2 to 134.7 °C, and a slight increment in the storage modulus (E') from 2.45 to 2.50 MPa when compared with irradiated matrix. These findings were also supported by field emission scanning electron micrography (FESEM) and transmission electron microscope (TEM), where distribution and disaggregation of nanofillers was observed. X-ray diffraction (XRD) showed greater intensity with the addition of CNT and EB radiation. The prototype of the outer sole HDPE/EPR–CNT nanocomposite showed an improvement in the flexing test, where it had the highest number of counts, indicating the ability of the prototype to withstand a bending force at a specific angle until it fully cracks. The enhancement of mechanical and thermal properties of irradiated HDPE/EPR-3 wt% CNTs established the development of high-performance lightweight nanocomposite sport shoe soles.